Contarinia manii sp. n. (Diptera, Cecidomyiidae): inducer of a remarkable gall on Acacia ferruginea in southern India - Harris, Keith M. (Zootaxa, 2010)
Contarinia manii (Diptera: Cecidomyiidae) is described as a new species, on the basis of adults reared from remarkable ’cylinder-piston’ galls formed from contiguous leaflets of Acacia ferruginea D.C. in southern India. These galls have been known since 1952 but adults were not reared until 2007. The new species, and another Indian species, Contarinia ramachandrani (Mani), induce similar but distinct galls on the same host plant. A third species, Contarinia carolinae Gagné, induces leaf galls on Acacia senegal in Kenya. Comparison of adult, pupal and larval morphology indicate that these three species may represent a monophyletic group associated with complex leaf galls on Acacia, in East Africa and India.